2020
DOI: 10.1175/wcas-d-19-0138.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns of Human Thermal Comfort Conditions in Russia: Present Climate and Trends

Abstract: The assessment of bioclimatic conditions at the national scale remains a highly relevant task. It might be one of the main parts of the national strategy for the sustainable development of different regions under changing climatic conditions. This study evaluated the thermal comfort conditions and their changes in Russia according to gridded meteorological data from ERA-Interim reanalysis with a spatial resolution of 0.75° × 0.75° using the two most popular bioclimatic indices based on the human energy balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 72 publications
1
11
0
1
Order By: Relevance
“…The increase in temperature for the warm period of 1997–2019 was weakly manifested, but affected the growth in the sum of ET required for the replication of the virus ( Table 5 ). Though the 22 year period might be a short time span to consider climate change, our results are in line with other studies that were made for a longer period and indicated a current warming trend in southern Russia [ 104 , 105 ]. At the same time, the durations of the SET and SEI were marginally shorter, although these changes were not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…The increase in temperature for the warm period of 1997–2019 was weakly manifested, but affected the growth in the sum of ET required for the replication of the virus ( Table 5 ). Though the 22 year period might be a short time span to consider climate change, our results are in line with other studies that were made for a longer period and indicated a current warming trend in southern Russia [ 104 , 105 ]. At the same time, the durations of the SET and SEI were marginally shorter, although these changes were not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…En Cuba la temperatura media del aire aumentó 1 ºC en el período 1951-2017 y se evidenció en el período 1981-2017 un aumento de los períodos cálidos y una disminución de los fríos (CITMA, 2020). En correspondencia, otras investigaciones realizadas en Rusia y China muestran resultados similares en cuanto a las tendencias que se están observando en índices bioclimáticos como el UTCI y PET (Wu et al, 2017;Varentsov et al, 2020).…”
Section: La Temperatura Efectiva Equivalente En Cubaunclassified
“…Its minimum of mean UTCI in winter does not coincide the temperature minimum and is shifted to the Arctic Ocean, where local extrema below −50 • C are found. Such a mismatch is explained by high sensitivity of the UTCI index to wind speed, and by strong and persistent wind at the Arctic coast in winter (Varentsov et al 2020).…”
Section: Thermal Comfort During Summer and Wintermentioning
confidence: 99%
“…For example, winter warming in north-western Russia is strongly expressed in terms of UTCI than in terms of temperature, while the rates of mean summer PET growth in south-western Russia exceed than the rates of the temperature growth. Such amplified rates of the UTCI and PET changes indicate the additional contribution from the long-term changes of other meteorological factors including wind speed and cloudiness (Varentsov et al 2020).…”
Section: Tracking Main Changes In Thermal Comfortmentioning
confidence: 99%